2022
DOI: 10.1039/d2cc02578g
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne insertion into Cu–Al bonds and selective functionalization to form copper acyl compounds

Abstract: We report on the insertion of alkynes into heterometallic M–M' bonds, producing (aluminylalkenyl)copper compounds which possess differential reactivity at the two derived M–C functions. Uniquely, this system is capable of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“… Sketched stationary point structures along the paths of Figure 1 with selected interatomic distances (Å) and bond angles (°). Values in parentheses refer to experimentally available data taken from ref ( 9 ). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Sketched stationary point structures along the paths of Figure 1 with selected interatomic distances (Å) and bond angles (°). Values in parentheses refer to experimentally available data taken from ref ( 9 ). …”
Section: Resultsmentioning
confidence: 99%
“…The syn dimetallated alkenes (9-Cu, 11-Cu) can give a selective insertion of CO leading to the formation of copper acyl compounds. 9 Strictly related gold silyl 10,11 and boryl 12 complexes have been also experimentally reported to insert alkynes into Au−Si and Au−B bonds. Amgoune and Bourissou reported that alkynes can be activated via insertion into the Au−Si bond of the gold silyl (R 3 P)AuSiR'Ph .…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations